Analisis Perbandingan ¬Tingkat Kesehatan Bank BUMN dan Bank BUSN Dengan Menggunakan Pendekatan Risk Based Bank Rating (RBBR) - Theresia Ella Sari; Yuniorita Indah Handayani; Nurshadrina Kartika Sari (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study aims to determine the effect of the Comparison of Health Levels of BUMN and BUSN Banks Using a Risk Based Bank Rating (RBBR) Approach. The data used in this study are secondary data obtained from the financial statements of BUMN and BUSN. Samples taken were 6 banks (3 BUMN Banks and 3 BUSN Banks) with purposive sampling method. The data obtained is then processed using the calculation of each variable based on the RBBR approach which refers to Circular Letter of OJK No.14/SEOJK.03/2017 covering components: Risk profile (using NPL ratio, LDR), Governance, Rentability (using ROA, ROE) and Capital (using CAR ratio).The results of the study show that in 2013-2017 the total composite ranking score of the entire BUMN Bank variable was higher than the BUSN Bank. The composite variable total score of ROA and ROE of BUMN banks is higher than BUSN. Total NPL, LDR, and GCG composite rating scores of BUSN Banks are higher than BUMN Banks. In the total composite rating score, the CAR variable of the BUMN Bank and BUSN Bank gets the same score.